2008
DOI: 10.1179/174328108x284589
|View full text |Cite
|
Sign up to set email alerts
|

In situstudies of agglomeration between Al2O3–CaO inclusions at metal/gas, metal/slag interfaces and in slag

Abstract: Studies of inclusion behaviour at the metal/slag interface is of great importance for the steel industry in order to achieve better control of both the size and amount of the inclusions, as well as improving the steel quality and the casting process. In this work agglomeration of liquid Al 2 O 3 -CaO particles at both steel/argon gas and steel/slag interfaces was studied with a confocal scanning laser microscope. In addition, agglomeration of liquid Al 2 O 3 -CaO-SiO 2 inclusions present in the slag was invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…All the experimental results were located in pure liquid oxide phase The inclusions with a liquid oxide outer layer were also easy to polymerize and floate up. 61,62) Thus, the magnesium content, aluminum content, and titanium content could be controlled within a reasonable range to promote the formation of MgO-Al 2 O 3 -Ti 3 O 5 liquid oxide inclusions during Ti-stabilized stainless steelmaking process, which would help to improve the cleanliness of molten steel.…”
Section: Thermodynamic Calculation Of Inclusion Formationmentioning
confidence: 99%
“…All the experimental results were located in pure liquid oxide phase The inclusions with a liquid oxide outer layer were also easy to polymerize and floate up. 61,62) Thus, the magnesium content, aluminum content, and titanium content could be controlled within a reasonable range to promote the formation of MgO-Al 2 O 3 -Ti 3 O 5 liquid oxide inclusions during Ti-stabilized stainless steelmaking process, which would help to improve the cleanliness of molten steel.…”
Section: Thermodynamic Calculation Of Inclusion Formationmentioning
confidence: 99%
“…Arai et al 24) reported that the particles with the large contact angle against the solvent easily attach to the bubbles and are more likely to be removed. Yin et al 40) and Wikström et al 41) observed the inclusion behavior at the metal/gas interface reporting that attraction force was applied between the solid inclusions which are not wet with the molten steel. On the other hand, attraction force was not applied between the liquid inclusions which can intimately wet with the molten steel.…”
Section: Rh Treatmentmentioning
confidence: 99%
“…Many efforts have been done to optimize steelmaking technologies to control the amount, size, and chemical compositions of non-metallic inclusions in molten steel, such as the formation, [5][6][7][8][9][10][11][12][13] modification, [14][15][16][17][18][19] and removal [20][21][22][23] of inclusions in molten steel. Less attention has been paid to the formation mechanism of oxide inclusions during the solidification of steel.…”
Section: Introductionmentioning
confidence: 99%